β2 -Microglobulin Levels in Patients with Postmenopausal Osteoporosis - Funda Taşçıoğlu; Yıldıray Tabak; Pınar Ulaşan; Cengiz Öner (Galenos Yayinevi, 2003)
The aim of this study was to evaluate the concentrations of b2 microglobulin in patients with postmenopausal osteoporosis and compare the results with the ones obtained from healthy postmenopausal women. We also evaluated the relationships between b2 microglobulin and bone mineral density (BMD), parathyroid hormone (PTH), calcium (Ca), phosphorus (P), alkaline phosphatase (ALP), and 24 hr urinary calcium levels. For this aim, 31 postmenopausal women with osteoporosis and 22 healthy postmenopausal women were included in the study. DXA was used for the measurement of BMD of the lumbar spine and proximal femur. Laboratory assessments included serum Ca, P, ALP, PTH, b2 microglobulin levels and 24 hour urinary calcium. BMD at the lumbar spine (p< 0.001), femur neck (p<0.001), ward triangle (p<0.001), and trochanteric region (p<0.05) was significantly lower and serum b2 microglobulin (p<0.05), alkaline phosphotase (p<0.05), and parathyroid hormone (p<0.05) levels were found to be significantly higher in postmenopausal osteoporotic women as compared to healthy controls. However, b2 microglobulin was not associated with BMD at any of the measured regions and no association was found between serum PTH, ALP, Ca, P, and 24 hour urinary calcium values. Although high levels of b2 microglobulin in postmenopausal osteoporotic women suggest that it might reflect osteoclastic activity, the possible role of this polypeptide in the pathogenesis of increased bone resorption, needs further investigation.